Update and prognosis of Dermacentor distribution in Germany: Nationwide occurrence of Dermacentor reticulatus - Springer, Andrea; Lindau, Alexander; Probst, Julia; Drehmann, Marco; Fachet, Katrin; Thoma, Dorothea; Rose Vineer, H.; Noll, Madeleine; Dobler, Gerhard; Mackenstedt, Ute; Strube, Christina (Frontiers in Veterinary Science, 2022)
A considerable range expansion of Dermacentor reticulatus has been observed in several European countries, which is concerning in the light of its vector function for several pathogens, including Babesia canis and tick-borne encephalitis virus (TBEV). The present study provides an update on the distribution of Dermacentor ticks in Germany, using a citizen science approach. Ticks were collected by participating citizens from March 2020 to May 2021, and submitted along with information on the date and location of collection, potential hosts and details about the circumstances of discovery. In total, 3292 Dermacentor specimens were received, of which 76.4% (2515/3292) were identified as D. reticulatus and 23.0% (758/3292) as D. marginatus, while 0.6% (19/3292) were too damaged for species-level identification. Dermacentor reticulatus was received from all federal states of Germany. Maxent species distribution models predicted suitable environmental conditions for D. reticulatus throughout Germany. Findings on the vegetation or on pastured animals without travel history confirmed the occurrence of this tick species as far north as the most northern German federal state Schleswig-Holstein. In contrast, the distribution of D. marginatus still seems to be limited to southwestern Germany, although the northward shift of the distribution limit observed in the preceding citizen science study, as compared with previous published distributions, was confirmed. This shift was also predicted by Maxent species distribution models, reflecting the broader distribution of the tick occurrence data contributed by citizens. Most D. reticulatus ticks were found on dogs (1311/1960, 66.9%), while D. marginatus was mainly discovered on hoofed animals (197/621, 31.7%) and humans (182/621, 29.3%). Human tick bites were reported in 0.7% (14/1960) of host-assigned D. reticulatus and 3.4% (21/621) of host-assigned D. marginatus. Further studies to investigate an increasing endemisation of Babesia canis in Germany as well as the relevance of D. reticulatus for TBEV spread throughout the country, e.g. by travelling dogs, are urgently needed. In view of the activity of D. reticulatus during winter or the colder months, which complements that of Ixodes ricinus, a year-round tick protection of at least dogs is strongly recommended.